2014 47th Hawaii International Conference on System Sciences 2014
DOI: 10.1109/hicss.2014.410
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Acceptance of Cloud Computing in SMEs: Towards a Valence Model of Relevant Factors

Abstract: Cloud Computing provides great opportunities especially for companies within the SME segment. This is why Cloud Service Providers (CSPs) are increasing their efforts to make their infrastructure accessible for small companies to help them compensate the lack of their own IT infrastructure. But nevertheless a lot of companies -especially smaller ones -are not yet convinced of the benefits of cloud services. This paper explores factors that influence the diffusion and acceptance of Cloud Computing among SMEs. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 16 publications
1
38
0
1
Order By: Relevance
“…TOE characterises the influence of organisational adoption of technological innovations by the technological context, the organisational context, and the environmental context. These contexts were also used by Nedbal et al to arrange important factors and ensure a broad scope of a theoretical model for sustainable outsourcing solutions (Nedbal et al, 2011) and by Stieninger and Nedbal (2014) as a basis for clustering influencing factors for diffusion and acceptance of cloud computing in SMEs. Strahringer (2009) provides a comprehensive overview of adoption factors consistently identified in literature, arranged according to the TOE framework.…”
Section: Drivers and Success Factors For The Adoption Of Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…TOE characterises the influence of organisational adoption of technological innovations by the technological context, the organisational context, and the environmental context. These contexts were also used by Nedbal et al to arrange important factors and ensure a broad scope of a theoretical model for sustainable outsourcing solutions (Nedbal et al, 2011) and by Stieninger and Nedbal (2014) as a basis for clustering influencing factors for diffusion and acceptance of cloud computing in SMEs. Strahringer (2009) provides a comprehensive overview of adoption factors consistently identified in literature, arranged according to the TOE framework.…”
Section: Drivers and Success Factors For The Adoption Of Innovationsmentioning
confidence: 99%
“…It is necessary to clarify terms and define its scope in advance to establish a consistent understanding, especially when analysing more recent and complex concepts like cloud computing (Stieninger and Nedbal, 2014). As literature reviews showed, there is a broad variety of definitions available (Yang and Tate, 2012).…”
Section: Cloud Computingmentioning
confidence: 99%
“…Some researchers proposed the implementation of the cloud computing technology based on the already existing TOE framework as shown in [36], [38]. Furthermore, the theory of Diffusion Of Innovation (DOI) has also been used [33]. Some researchers have proposed the process of studying the implementation of cloud computing based on the already defined two models together in a combined form [33], [37].…”
Section: Cloud Computing Adoption In Organizationsmentioning
confidence: 99%
“…The support of software functionalities, the ubiquitous access to data, responsive solutions to customer support queries, maintaining huge data and reducing cost are key success factors for organization's customers to adopt cloud computing [32]. Stieninger and www.ijacsa.thesai.org Nedbal [33] depicted that the factors influencing an implementation of cloud computing are perceived by safety and security, cost, trust management, and efficiency of energy. Hussein et al [34] used qualitative and quantitative methods to investigate the awareness of cloud computing within SMEs present in Malaysia.…”
Section: Cloud Computing Adoption In Organizationsmentioning
confidence: 99%
“…Cloud security Gangwar et al, 2015;Li et al, 2015;Oliveira et al, 2014;Ross & Blumenstein, 2015;Safari et al, 2015;Stieninger & Nedbal, 2014;Tang and Liu, 2015;Tarmidi et al, 2014;Tehrani & Shirazi, 2014;Zhao et al, 2014Anthony, 2012DBCDE, 2013;DFD, 2011bDFD, , 2011cDFD, , 2011dDOC, 2014;IMO, 2012;IMO, 2013;ITIIC, 2011;Jansen & Grance, 2011;SWI, 2012ACCA, 2014Ben, 2014;Dave, 2012;Handler et al, 2012;Herhalt & Cochrane, 2012;Hutley, 2012;Mark, 2011;Minifie, 2014;Pearson, 2012;Ren et al, 2012;Telstra, 2011 Cloud privacy Fairchild, 2014;Fakieh et al, 2014;Gangwar et al, 2015;Kauffman et al, 2014;Mahmood et Anthony, 2012;DBCDE, 2013;DFD, 2011bDFD, , 2011cDFD, , 2011d…”
Section: Constructs Academic Government Practitionermentioning
confidence: 99%